Future of reproductive biotechnologies in water buffalo in Southeast Asian countries - Hufana-Duran, Danilda; Chaikhun-Marcou, Thuchadaporn; Duran, Peregrino G.; Atabay, Eufrocina P.; Nguyen, Hong Thi; Atabay, Edwin C.; Nguyen, Uoc Thi; Nguyen, Hiep Thi; Hiew, Mark W.H.; Punyawai, Kanchana; Ginting, Nurzainah; Parnpai, Rangsun (Elsevier, 2025)
The future of reproductive biotechnologies in water buffalo in Southeast Asian countries holds significant promise for enhancing genetic quality and productivity. Fixed-time artificial insemination remains the commonly used technology, with advances in assisted reproductive technologies (ART) such as in vitro embryo production (IVEP), embryo transfer (ET), and the use of sex-sorted sperm increasingly adopted to improve breeding efficiency. These technologies overcome traditional breeding limitations, such as low reproductive rates, genetic diversity constraints, and the production of sex-predetermined offspring. The application of multiple ovulation and embryo transfer (MOET) is constrained by poor embryo recovery in this livestock species. Somatic cell nuclear transfer (SCNT) offers great potential for producing sex-predetermined and genetically superior buffalo but requires further research to increase efficiency. Cryopreservation of buffalo genetics is bolstered by the establishment of Gene Banks. Challenges such as high costs, the need for skilled personnel, and infrastructure development remain constraints. Integration of genomic selection, automation, and expansion of ET programs are clear directions. Strengthening research and collaboration among Southeast Asian countries is essential to fully realize the benefits of these biotechnologies and ensure sustainable and profitable buffalo farming.